A comprehensive study on effective triple‐phase boundary density and its correlation with active anode thickness in solid oxide fuel cells - Shingruf Shaukat; Asif Nadeem Tabish; Muneeb Irshad; Samina Akbar; Iqra Farhat; Liyuan Fan (Energy Science & Engineering)
Abstract Solid oxide fuel cells (SOFCs) are highly promising devices for efficient and low‐emission energy conversion. The effective triple‐phase boundary (TPB) density refers to the fraction of percolated TPB density that effectively contributes to the current production during cell operation. This is one of the most fundamental and least understood aspects of the cell design and performance assessment. This study methodically investigates the effective TPB density, using a computational fluid dynamics model based on the TPB‐based kinetics and its correlation with the active anode thickness. Experimental data from previously published studies with varying thicknesses of anode functional layer and operating regimes are utilized to validate the model. The results of this study reaffirm that a significant fraction of the percolated TPB density in SOFCs remains unused during cell operation. This finding emphasizes the need to consider the effective TPB density for theoretical and experimental investigations focusing on optimizing cell performance. Furthermore, an inverse relationship is observed between the effective TPB density and the active anode thickness; a lower active anode thickness corresponds to a higher effective TPB density and vice versa. These findings contribute to advancing sustainable energy systems by guiding the development of more efficient SOFC designs and operational strategies that effectively utilize TPB sites.